The Relationship Between Quality of Food and Nutrition Services and Patient Loyalty with Mediated Patient Satisfaction at X Hospital Bogor - Rini Siti Haerani; Idrus Jus’at; Anastina Tahjoo (Penerbit Kemala Indonesia, 2020)
Hospital’s success depends on patients’ expectations, perception, and judgment on the quality of services provided by hospitals. The study aims to determine the suitability between expectations and perceptions quality of food and nutrition service which is received by patients during inpatient care at X Hospitals and to analyze the relationship between quality of food and nutrition services and patient loyalty that is mediated by patient satisfaction. This research used a longitudinal prospective survey with a quantitative approach and simple random sampling. The sample of this study consists of 35 elderly inpatients 60 years old and over and at least three days of being hospitalized. The data required was collected through the standard SERVQUAL, satisfaction, and loyalty questionnaire and then it was path analyzed using the SPSS software. The result of the study showed the average perceived congruence between perceptions and expectations of the quality of food and nutrition services was 95.22%. The correlation analysis shows all of the relationship independent and dependent variables have a positive and significant pattern (p